PP.71 Active Drug Use Vs Replacement Therapy or Abstinence During Pregnancy: Impact on the Outcomes For Mothers and Babies. (26th April 2013) - Doohan, M; Dwyer, N; Farey, J
Abstract : Aims: To evaluate demographic characteristics of women with history of substance misuse, analyse the differences in the birth weights (term baby) amongst continuous drug users and the abstinent (or on replacement treatment) mothers, and to identify key factors associated with placement of neonate under social services care. Methodology: Data was collected retrospectively from a database set up by the Bristol Specialist Drugs and Alcohol Service for all pregnant women with illicit drug use between April 2010 and March 2011. Results: Sixty-two women attended the specialist substance misuse antenatal clinic. Only 50% of the women without replacement therapy were first seen within 12 weeks of gestation. Term babies born to mothers who were on replacement therapy or showed abstinence were 350 grammes heavier (3.1 kg vs. 2.75 kg) than the babies born to ongoing illicit drug using group. 73% of neonates whose mothers were still misusing drugs at the time of delivery were taken into care. Postpartum average length of stay for mothers abusing illicit drug during pregnancy was 8.4 days vs. 5.5 days in the abstinent or replacement therapy group. Babies born to mothers using illicit drugs stayed in hospital for an average of 12.3 days compared to 5.5 days for the other group. Conclusions: This study provides some initial data, which can be used for patient education and awareness training for a variety of professionals regarding importance of early booking, and evidence based advice to remain abstinent or on replacement therapy, to improve the outcomes of the pregnancy.